HER-2/neu analysis in breast cancer bone metastases. Issue 6 (27th May 2009) - Zustin, J; Boddin, K; Tsourlakis, M C; Burandt, E; Mirlacher, M; Jaenicke, F; Izbicki, J; Ruether, W; Rueger, J M; Bokemeyer, C; Simon, R; Sauter, G
Abstract : Background: HER-2 is the target for antibody-based treatment of breast cancer (trastuzumab), which is highly successful in both advanced disease and the adjuvant setting. HER-2 can be analysed by fluorescence in situ hybridisation (FISH) for gene amplification or immunohistochemistry (IHC) for protein overexpression. Aim: As both methods are known to be influenced by previous tissue processing, to analyse the applicability of both FISH and IHC to decalcified bone metastases of breast cancer. Methods: A tissue microarray (TMA) was constructed from 149 breast cancer bone metastases. Consecutive TMA sections were analysed by FISH (PathVysion) and IHC (HercepTest). Results: FISH analysis was interpretable in 113 (85.0%) cases. Amplification was seen in 14 (12.4%) interpretable metastases. HER-2 positivity on IHC analysis was 3+ in 9.8% of cases and 2+ in 11.3%. A comparison of the two techniques revealed high concordance. Of the 14 cases of amplification, 10 (71%) showed 3+ IHC staining, two (14%) showed 2+, one (7%) showed 1+, and one (7%) showed 0+. Three of the four amplified cases that did not show 3+ IHC staining had an equivocal FISH result, with a HER-2/centromere 17 ratio of 1.8–2.2. Of the 13 cases that showed IHC 3+ staining, amplification was present in 10 (77%). Conclusions: HER-2 FISH analysis has an excellent success rate in highly standardised EDTA-decalcified bone metastases, suggesting that this method is easily applicable to decalcified tissues. The high concordance between IHC and FISH suggests that HER-2 IHC may be equally applicable to EDTA-treated tissues as to the usual formalin-fixed tissues.